2004
DOI: 10.1091/mbc.e04-01-0041
|View full text |Cite
|
Sign up to set email alerts
|

Cbl-dependent Ubiquitination Is Required for Progression of EGF Receptors into Clathrin-coated Pits

Abstract: Ligand binding causes the EGF receptor (EGFR) to become ubiquitinated by Cbl upon association with the adaptor protein Grb2. We have investigated the role of ubiquitin and Grb2 in ligand-induced endocytosis of the EGFR. Incubation of cells with EGF on ice caused translocation of Grb2 and Cbl from the cytosol to the rim of coated pits. Grb2 with point mutations in both SH3 domains inhibited recruitment of the EGFR to clathrin-coated pits, in a Ras-independent manner. On overexpression of the Cbl-binding protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
170
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(183 citation statements)
references
References 55 publications
13
170
0
Order By: Relevance
“…These latter findings also indirectly stress the importance of Cbl-executed ubiquitination of other downstream endocytic proteins for proper clathrin endocytosis. A recent report by Stang et al (25), which shows that Cbl-dependent ubiquitination is required for progression of the EGFR into coated pits, further reinforces this notion. Taken together with these results, our findings suggest a mechanism through which ubiquitination of endocytic machinery, but not cargo ubiquitination, is required for internalization into coated pits.…”
Section: Discussionmentioning
confidence: 59%
“…These latter findings also indirectly stress the importance of Cbl-executed ubiquitination of other downstream endocytic proteins for proper clathrin endocytosis. A recent report by Stang et al (25), which shows that Cbl-dependent ubiquitination is required for progression of the EGFR into coated pits, further reinforces this notion. Taken together with these results, our findings suggest a mechanism through which ubiquitination of endocytic machinery, but not cargo ubiquitination, is required for internalization into coated pits.…”
Section: Discussionmentioning
confidence: 59%
“…We have found that ubiquitination of the EGFR is necessary for its recruitment into coated pits (Stang et al, 2004). It has been found that ubiquitination of the EGFR by Cbl can occur both via the direct interaction between the EGFR and Cbl and via indirect interactions through Grb2 (Waterman et al, 2002).…”
Section: Ubiquitination and Endocytosismentioning
confidence: 92%
“…Epsin is localized to clathrin-coated pits (Stang et al, 2004;Hawryluk et al, 2006) and has been found to be involved in clathrin-mediated endocytosis Wendland et al, 1999). Whereas some authors have proposed that epsin functions as an adaptor in clathrin-mediated endocytosis (reviewed in Wendland, 2002), others have shown that epsin is involved in the formation of membrane curvature within clathrincoated pits.…”
Section: Additional Adaptor Proteins In Clathrin-mediated Endocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…de Melker et al 2004;Stang et al 2004;Sigismund et al 2005 membrane -cytosol interface (Jahnke et al 2012;Kajikawa et al 2012). Another major class of E3 ligases is the neural precursor-cell-expressed, developmentally down-regulated 4 (Nedd4) family, which contains a catalytic HECT (homologous E6-AP carboxy-terminal) domain (Rotin and Kumar 2009).…”
Section: Eps15mentioning
confidence: 99%